Synthesis and Anticonvulsant Activity Evaluation of 2-Phenyl-2H-benzo[e][1,3]oxazin-4(3H)-ones - Cui, Li-Jing; Guo, Jun; Gong, Guo-Hua; Quan, Zhe-Shan (Asian Journal of Chemistry, 2014)
A series of new 2-phenyl-2H-benzo[e][1,3]oxazin-4(3H)-one derivatives (1a-1t) were designed based on the known anticonvulsant activity of quinolinone derivatives. All target compounds 1a-1t, characterized by IR, 1H NMR and MS, have been evaluated for their anticonvulsant activity against MES-induced seizures. The pharmacological results showed that all the compounds displayed some degree of anticonvulsant activity. Among them, 2-phenyl-2,3-dihydrobenzo[e][1,3]oxazin-4-one (1a) and 2-(2-fluorophenyl)-2,3-dihydrobenzo[e][1,3]oxazin-4-one (1b) were considerd more promising because of their lower ED50 (34.1 and 28.4 mg/kg) and higher protective index (11.1 and 8.0).